The Together Research: Exploring Substantive Equality in Disability-Led Performing Arts Research in Western Australia - Hales, Julia; Fox, Sam; Newman, Renée; Flavelle, Simone (Performance Matters, 2025)
This article presents case findings from the ongoing Together Research project based in Boorloo/Perth (Western Australia). This co-designed and participatory project is led by artists and researchers of the creative My Studio program at My Place, an organization that supports people living with disability. The project investigates the evolving practices of substantive equality and agency in the Australian arts sector. We do this through workshops that explore concepts of genuine equity for disabled artists, creative control taken by disabled artists, and empowered collaboration with nondisabled allied artists.Here, we first discuss My Studio and then focus on a specific workshop called Movement Together, which was led by My Studio artists in partnership with STRUT Dance in 2024. The workshop facilitated peer-to-peer exchange, accessible co-creation, and dance improvisation involving twelve nondisabled dance artists and eight artists living with disabilities. Co-facilitated by artists Julia Hales and Sam Fox, the workshop served as a platform for interrogating the values, ethics, and methods of the Together Research project.We reflect on the experiences of the Movement Together workshop and envision future implementations of core principles regarding movement creation and dramaturgical approaches to directing that are accessible, collaborative, and disability-led, addressing the distinct area of disadvantage for artists who have not had access to tertiary training due to the barriers of accessibility. The core principles we have developed, which contribute to what Alison Kopit, Ann Marie Dorr, and Maggie Bridger name “access dramaturgy,” emphasize in particular how accessibility means little without creative agency and substantive equality for people living with disability, particularly if attempts to dislodge systemic advantage for the “majority” are not actively made. The findings and examples provided here have been generated with the broader performing arts industry in mind, offering direct and actionable statements made developed by the Together Research artists.Plain Language Abstract (adapted by Kelsie Acton with Daniel Foulds)The Together Research is led by artists and researchers at the My Studio program at My Place. My Place is an organization that supports people living with disability. The Together Research wants artists with disabilities tohave access to the arts, be treated fairly, have control over their work.This essay is about the Movement Together workshop. STRUT Dance created the Movement Together Workshop. Julia Hales and Sam Fox ran the workshop. They used improvisation, where people dance and don’t decide how to move ahead of time. There were eight nondisabled artists and eight artists living with disabilities. Both nondisabled artists living with disabilities led the creation. The workshop was a way of figuring out artists’ shared values. This essay shares what happened at the workshop. We also think aboutaccess dramaturgy, the idea that access should be part of the process of making art; and how access doesn’t mean anything unless disabled artists have control and choices.